Case report: Deep vein thrombosis as the sole clinical feature of Behcet’s syndrome - Omara, Abdelrahman; Alkhuboli, Mohamed; Nauman, Javaid; Al Nokhatha, Shamma; Almarshoodi, Mozah (Frontiers in Medicine, 2023)
Introduction Behcet’s syndrome is a rare, chronic, systemic condition often categorized within the group of vasculitides. It presents a diagnostic challenge due to its varied clinical manifestations and the absence of a definitive laboratory test. Its etiology remains unclear but may involve genetic, infectious, and environmental factors. Case presentation We report the case of a 16-year-old male who presented with deep vein thrombosis, followed by recurrent episodes of breakthrough thrombosis, despite adequate anticoagulant therapy. The patient did not meet the International Study Group (ISG) criteria nor the International Criteria for Behcet’s syndrome (ICBD) due to the absence of characteristic features such as oral aphthous ulcers, genital ulcers, and uveitis. Later in the disease course, after ruling out other causes of breakthrough thrombosis, he tested positive for HLA-B51, an allele associated with Behcet’s syndrome, and exhibited a pathergy reaction. Discussion The patient’s clinical course underlines the diagnostic complexity associated with Behcet’s syndrome and highlights the importance of maintaining a broad differential diagnosis in cases of recurrent thrombosis. Although HLA-B51 testing is not routinely recommended, it played a pivotal role in our case, underscoring the value of an integrated diagnostic approach. Furthermore, this case reinforces the potential for atypical presentations of Behcet’s syndrome, necessitating vigilant clinical awareness. After establishing the diagnosis, we successfully treated the patient with immunosuppressive therapy, significantly improving his condition.